Effectiveness of mindfulness-based audio-visual interventions on self-efficacy in childbirth readiness among high-risk pregnant women - Aisyah Nur Fitri, Aisyah Nur Fitri; Misrawati, Misrawati; Erika, Erika; Hasan, Haliza (Palembang MediRose Publisher, 2025)
Background: High-risk pregnancies in women under 20 or over 35 years are commonly associated with low self-efficacy, leading to anxiety, poor coping, and inadequate childbirth readiness. Few studies have targeted interventions to directly improve self-efficacy, and mindfulness delivered through audiovisual media represents a promising yet underutilized approach to enhance psychological preparedness in this population.